2002
DOI: 10.3758/bf03195264
|View full text |Cite
|
Sign up to set email alerts
|

What information underlies correct rejections in short-term recognition memory?

Abstract: We propose that correct rejections are based on information that contradicts the study set, rather than on insufficient familiarity. Using two-dimensional stimuli, we varied the featural overlap between lures and the study set so that one feature of the lure had occurred during study and the second feature of the lure had not occurred. Familiarity varied with the number of times the studied feature had occurred, whereas detectability of the extralist feature varied with the number of studied alternatives on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…Thus, while the data for these exams arise from test administrations "in the wild" rather than in controlled laboratory settings, the possibility of priming effects for student performances exists, akin to those seen in memory research. 30 Another trend exemplified in these data involves the pattern of the difficulty index for previous items. For students taking the blue exam, item difficulty index on the previous three items is, on average, lower than for the three preceding items on the gray exam.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Thus, while the data for these exams arise from test administrations "in the wild" rather than in controlled laboratory settings, the possibility of priming effects for student performances exists, akin to those seen in memory research. 30 Another trend exemplified in these data involves the pattern of the difficulty index for previous items. For students taking the blue exam, item difficulty index on the previous three items is, on average, lower than for the three preceding items on the gray exam.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The traditional view has been challenged by a series of experiments using stimuli that permit one to measure and manipulate the featural overlap among stimulus items (Johns & Mewhort, 2002b;Mewhort & Johns, 2000). In a critical experiment (Mewhort & Johns, 2000, Experiment 3), each study list comprised four items defined by their values on two dimensions: Aa, Ab, Bc, Cc, where A, B, and C represent the values on the first dimension and a, b, and c represent the values on the second.…”
mentioning
confidence: 99%
“…That is, subjects base negative decisions on contradiction rather than on lack of familiarity: If an aspect of the probe that contradicts the study set can be identified, the subject will respond "no." Subsequent work indicated that an extralist feature is easier to identify the fewer the studied values occurring on that dimension (Johns & Mewhort, 2002b).…”
mentioning
confidence: 99%
See 2 more Smart Citations